ANALISIS KINERJA PERUSAHAAN DENGAN METODE BALANCED SCORECARD - Kulsum, Yelika; Idayati, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to measure the performance of the company by analyzing and evaluating the performance of PT Kereta Api Indonesia Daerah Operasi 8 Surabaya by using Balanced Scorecard method as the performance measurement instrument. This measurement is done by using four perspectives i.e.: financial, customer, internal business, and growth and learning. This research is qualitative descriptive research. The data collection technique is done by performing field survey, questionnaires, observation, and interview.The result of financial perspective shows that return of investment undergoes reduction since the company undergoes quite large asset enhancement so it reduces profit. Meanwhile, the calculation of gross profit margin and operating profit margin shows quite well result. Based on the customer perspective, it shows quite well result when it is considered from the respond of the customer, based on the internal business perspective, it shows quite well result, and based on the growth and learning perspective, it has been found from the retention of the employees shows a less good performance when it is considered from the number of employees which decreases every year. Meanwhile, it can be categorized quite well when it is considered from the percentage of employees who participate in training.Keywords:Balanced Scorecard, Company Performance, Customer Satisfaction, Performance Assessment